The Physicochemical and Sensory Attributes of Watermelon Rind Flour Incorporated Steamed Cupcake - Ho, Lee Hoon; Mazlyani, Paet; Mazaitul Akma, Suhaimi (2018)
This study aim to investigate the physicochemical and sensory attributes of watermelon rind flour incorporated steamed cupcakes. The produced watermelon rind flour using hot-air drying at 40, 60°C and freeze drying were substituted for plain flour at 10% level to produce CR40, CR60, and CRFD, respectively. Steamed cupcake without watermelon rind flour served as control (CCONT). Proximate results showed that composite steamed cupcakes had significantly (p<0.05) higher ash, crude fat, and crude fibre contents but lower crude protein, total carbohydrate, and calorie values than control. CRFD steamed cupcakes showed lighten crust and crumb and greater volume and specific volume. However, it shows harder texture but springier crumb than the CCONT. Sensory evaluation results showed that all steamed cupcakes with or without containing 10% watermelon rind flour were considered acceptable by the panellists. It can be concluded that watermelon rind flour dried using freeze drying method improved the nutritional quality and texture properties of steamed cupcakes.